2020
DOI: 10.1108/jpmh-06-2020-0062
|View full text |Cite
|
Sign up to set email alerts
|

Winter is coming: age and early psychological concomitants of the Covid-19 pandemic in England

Abstract: Purpose This paper aims to demonstrate early psychological concomitants of the Covid-19 pandemic in England on a sample of younger and older people. Design/methodology/approach A cross-sectional quantitative questionnaire (n = 1608) was conducted on the Prolific website. Participants completed the PERMA Scale (Flourishing), the four Office of National Statistics (ONS4) Well-being Questions, the Clinical Outcomes Measure in Routine Evaluation (CORE-10) and the short University of California Los Angeles Brief … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 30 publications
1
24
1
1
Order By: Relevance
“…Older adults reported a presence or worsening of psychological symptoms, and greater loneliness because of pandemic-related social isolation [ 33 , 38 , 47 , 49 , 51 , 52 , 56 , 57 , 62 , 63 , 77 , 78 , 84 , 89 , 90 , 99 , 105 , 114 , 117 , 128 , 135 , 139 , 140 , 148 , 156 , 160 ]. Compared to younger age, older age (ie, ≥60 years) was, however, associated with fewer psychological symptoms [ 39 , 44 , 50 , 54 , 57 , 59 , 64 - 67 , 74 , 77 , 89 , 95 , 97 , 98 , 101 , 107 , 109 , 111 , 114 , 116 , 120 , 121 , 124 , 125 , 127 , 136 , 138 , 147 , 151 , 153 , 157 , 158 , 161 , 162 , 165 ], lower loneliness [ 92 , 95 , …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Older adults reported a presence or worsening of psychological symptoms, and greater loneliness because of pandemic-related social isolation [ 33 , 38 , 47 , 49 , 51 , 52 , 56 , 57 , 62 , 63 , 77 , 78 , 84 , 89 , 90 , 99 , 105 , 114 , 117 , 128 , 135 , 139 , 140 , 148 , 156 , 160 ]. Compared to younger age, older age (ie, ≥60 years) was, however, associated with fewer psychological symptoms [ 39 , 44 , 50 , 54 , 57 , 59 , 64 - 67 , 74 , 77 , 89 , 95 , 97 , 98 , 101 , 107 , 109 , 111 , 114 , 116 , 120 , 121 , 124 , 125 , 127 , 136 , 138 , 147 , 151 , 153 , 157 , 158 , 161 , 162 , 165 ], lower loneliness [ 92 , 95 , …”
Section: Resultsmentioning
confidence: 99%
“…Older adults reported a presence or worsening of psychological symptoms, and greater loneliness because of pandemic-related social isolation [33,38,47 [92,95,104,130,140,159], and better mental health and well-being [95,106,126,157,161,162]. Older adults were also shown to be better at regulating their emotions and coping with stressful events [44,61,68].…”
Section: Personal Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…This group has been, and continuous to be, considered at risk for severe illness and mortality from COVID-19 infection ( Shahid et al, 2020 ; Gerwen et al, 2021 ) and therefore has had to incorporate changes into their day to day life. Health policies have targeted older people in asking them to isolate and physically distance to avoid infection which, although successful in protecting from the virus, have had negative consequences of their own: Increased subjective social isolation ( Peng and Roth, 2021 ), lower healthcare utilization ( Ksinan Jiskrova et al, 2021 ), reduction of physical activities ( Creese et al, 2020 ; Brown et al, 2021 ), and social interaction ( Richter and Heidinger, 2020 ; Heid et al, 2021 ) as well as the ever increasing problem of loneliness ( Carson et al, 2020 ; Entringer et al, 2020 ; Heidinger and Richter, 2020 ; Luchetti et al, 2020 ; Stolz et al, 2020 ; Krendl and Perry, 2021 ) have been reported as byproducts of COVID-19 safety measures. As these lifestyle changes have been previously linked to adverse mental health outcomes, it is not surprising that an increase in depression, anxiety and stress symptoms, and a general decline of mental health during the pandemic ( Shahid et al, 2020 ; Gerwen et al, 2021 ) have been noted in multiple studies ( Banks and Xu, 2020 ; Bailey et al, 2021 ; De Pue et al, 2021 ; Grolli et al, 2021 ; Tsoukalis-Chaikalis et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…As these lifestyle changes have been previously linked to adverse mental health outcomes, it is not surprising that an increase in depression, anxiety and stress symptoms, and a general decline of mental health during the pandemic ( Shahid et al, 2020 ; Gerwen et al, 2021 ) have been noted in multiple studies ( Banks and Xu, 2020 ; Bailey et al, 2021 ; De Pue et al, 2021 ; Grolli et al, 2021 ; Tsoukalis-Chaikalis et al, 2021 ). These issues seem to be greater in younger population cohorts ( Banks and Xu, 2020 ; Carson et al, 2020 ) but have been found to be universal among (western) populations.…”
Section: Introductionmentioning
confidence: 99%